Substantial effect of voluntary policy interventions on aircraft ground handling safety - Musa, M. (Elsevier Ltd, 2020)
Managing safety and health matters require comprehensive policy intervention to change the existing culture in the ground handling operations and reducing the safety performance outcomes. This study aims to investigate the relationship between safety culture and safety performance outcome with voluntary policy intervention as the moderating effect of the relationship. The study employed a quantitative method through a survey instrument, which was participated by 423 ground handling workers from six international airports in Malaysia. The results indicated seven hypotheses in direct relationships have positive association between safety culture and safety performance construct. While for moderator relationships, there were five hypotheses found to be statistically significant and supported. The presence of voluntary policy interventions were found to be beneficial or detrimental elements for the insignificant relationships of the study. The ground handling organisation is expected to utilise these results by strengthening their organisation safety culture and prioritise safety and health matters over demand and cost. Â© 2020 Elsevier Ltd